Karakteristik Arsitektural Bangunan Indis Pada Perumahan Pegawai PJKA Pengok Blok A & B di Yogyakarta - Fauza Hastati; Giska Ayu Pradana Putri Kamase; Pascaghana Jayatri Putra (Program Studi Arsitektur Fakultas Teknik Universitas Mataram, 2021)
Indis house is a designation for the living house that occupied by both Dutch and the Indo-Dutch that built in the Dutch Colonial age in style of combining between Europe architectural forms especially Dutch and local architectural (Java). This combining created architectural characteristics of Indis house that are different from traditional house. In planning and designing process, Indis house is influenced by many factors such as the condition of surroundings, tropical climate which are very different from the climate in Netherland, social status, and also combining forms between Europe architecture and local architecture. The housing of Pegawai Perusahaan Jawatan Kereta Api Pengok at block A and B in Yogyakarta as one of the Indis housing of Dutch Colonial inheritance has uniqueness that reflected on its setting whith background of many factors influenced it. This literatur uses rationalistic-qualitative metheod in approach to theoretical framework that is built base on assessment parameters of architectural characterictics of living house according to Habraken (1978) including spatial system, physical system, and stylistic system. The Housing of PJKA Pengok at Block A and B in Yogyakarta was influenced by arhitectural style from two periods of Indis architecture development in Indonesia, the first one is the period in 1800-1902 (the Empire Style), and the second one is the period in 1902-1920. It most influnced by sosial status of users that reflected on its physical building setting. This sosial status prevailed to inner that reflected on distinct separation between hoodgebouw and bijgebouw, and also the social status prevailed to outside was inter-occupants of the houses location based on level of positions in Centrale Werkplaats (Balai Yasa). Another factor that also influenced the architectural characteristics is local climate that makes this housing looks in characterictics of tropical house. Climate aspect is an essential consideration in Indis house as an effort to create freshness inside the house. Next, combining factors between Ducth architectural forms and the traditional (Java) also influenced the architectural setting. Europe forms seem at building elements like door, window, luifel, gevel, chimney, and floor while the local ones seem at pattern of figure ground, the existence of open space in form of front veranda, the compositition of open space and building, and also vegetation.